Discussing illicit drugs in public internet forums: Visibility, stigma, and pseudonymity. - Barratt, Monica (ACM, 2011)
It has been claimed that people discuss their own illicit drug use online because anonymity allows them to avoid the legal and social risks of identifying themselves as drug users. Discourses around the risks, strategies and management of online drug discussion were produced by interviewing 26 ‘party drug’ users who reported participating in internet forums where drugs were discussed. Three factors influenced the extent to which drug forum users discussed their own drug use in public internet forums: perceived visibility, perceived legal risk and social stigma, and perceived effectiveness of pseudonymity. Implications for internet research with drug users are discussed.